STUDY OF ROAD PERFORMANCE IN AHMAD YANI DUE TO MARKET ACTIVITIES IN PALANGKA RAYA CITY - Dony Setiawan; Revianti Coenraad (PARENTAS: Jurnal Mahasiswa Pendidikan Teknologi dan Kejuruan, 2023)
Road performance is a quantitative measurement that describes certain conditions that occur on a roadsegment. Generally, in assessing road performance, it can be seen from capacity, degree of saturation (DS).Road performance is usually influenced by several things such as side Side Barrier and so on. Indonesia HighwayCapacity Manual, explains that side barriers are an impact on traffic performance and activities on the side ofthe road segment, such as pedestrians (weight = 0.5), public vehicles or other vehicles stopping (weight = 1.0),vehicles exiting or entering the side of the road (weight = 0.7), slow vehicles (weight = 0.4). The number of sidebarriers that affect the road segment results in the emergence of delays which result in decreased roadperformance. The results of the study show that the performance of the road is saturated (DS>1) due to the sideobstacle that occur on A. Yani, street the market area of Palangka Raya City